Formation of nitrogenous disinfection by-products in 10 chlorinated and chloraminated drinking water supply systems - Liew, Deborah; Linge, Kathryn; Joll, Cynthia (Springer Netherlands, 2016)
The presence of nitrogenous disinfection by-products (N-DBPs) in drinking water supplies is a public health concern, particularly since some N-DBPs have been reported to be more toxic than the regulated trihalomethanes and haloacetic acids. In this paper, a comprehensive evaluation of the presence of N-DBPs in 10 drinking water supply systems in Western Australia is presented. A suite of 28 N-DBPs, including N-nitrosamines, haloacetonitriles (HANs), haloacetamides (HAAms) and halonitromethanes (HNMs), were measured and evaluated for relationships with bulk parameters in the waters before disinfection. A number of N-DBPs were frequently detected in disinfected waters, although at generally low concentrations (<10 ng/L for N-nitrosamines and <10 µg/L for other N-DBPs) and below health guideline values where they exist. While there were no clear relationships between N-DBP formation and organic nitrogen in the pre-disinfection water, N-DBP concentrations were significantly correlated with dissolved organic carbon (DOC) and ammonia, and these, in addition to high bromide in one of the waters, led to elevated concentrations of brominated HANs (26.6 µg/L of dibromoacetonitrile). There were significant differences in the occurrence of all classes of N-DBPs between chlorinated and chloraminated waters, except for HNMs, which were detected at relatively low concentrations in both water types. Trends observed in one large distribution system suggest that N-DBPs can continue to form or degrade within distribution systems, and redosing of disinfectant may cause further by-product formation.